(untitled) (American Journal of Innovation in Science and Engineering, 2023)
Managing inventory has become increasingly complex and intriguing in today’s business landscape. Companies are striving to optimize their warehousing while balancing various costs. As a result, inventory management is crucial to maintain product quality and meeting customer demands. This paper outlines an effective inventory management system that incorporates demand forecasting to prevent the issues of overstocking or understocking. Furthermore, a performance analysis illustrates how the inventory management system has become essential to the industry sector.